A novel pathway of direct methane production and emission by eukaryotes including plants, animals and fungi: An overview. (August 2015) - Liu, Jiangong; Chen, Huai; Zhu, Qiuan; Shen, Yan; Wang, Xue; Wang, Meng; Peng, Changhui
Abstract: Methane (CH4 ) is a powerful greenhouse gas with a global warming potential 28 times that of carbon dioxide (CO2 ). CH4 is responsible for approximately 20% of the Earth's warming since pre-industrial times. Knowledge of the sources of CH4 is crucial due to the recent substantial interannual variability of growth rates and uncertainties regarding individual sources. The prevailing paradigm is that methanogenesis carried out by methanogenic archaea occurs primarily under strictly anaerobic conditions. However, in the past decade, studies have confirmed direct CH4 release from three important kingdoms of eukaryotes—Plantae, Animalia and Fungi—even in the presence of oxygen. This novel CH4 production pathway has been aptly termed "aerobic CH4 production" to distinguish it from the well-known anaerobic CH4 production pathway, which involves catalytic activity by methanogenic archaeal enzymes. In this review, we collated recent experimental evidence from the published literature and documented this novel pathway of direct CH4 production and emission by eukaryotes. The mechanisms involved in this pathway may be related to protective strategies of eukaryotes in response to changing environmental stresses, with CH4 a by-product or end-product during or at the end of the process(es) that originates from organic methyl-type compounds. Based on the existing, albeit uncertain estimates, plants seem to contribute less to the global CH4 budget (3–24%) compared to previous estimates (10–37%). We still lack estimates of CH4 emissions by animals and fungi. Overall, there is an urgent need to identify the precursors for this novel CH4 source and improve our understanding of the mechanisms of direct CH4 production and the impacts of environmental stresses. An estimate of this new CH4 source, which was not considered as a CH4 source by the Intergovernmental Panel on Climate Change (IPCC) (2013), could be useful for better quantitation of the global CH4 budget. Highlights: Literature of direct CH4 production and emission by eukaryotes were synthesized. Our review suggests an association among eukaryotes with direct CH4 production. Direct plant CH4 mission comprises 3–24% of the total annual CH4 emission.